Interest Rate Risk Management Elias S. W. Shiu Department of Statistics & Actuarial Science - PowerPoint PPT Presentation

slide1 n.
Download
Skip this Video
Loading SlideShow in 5 Seconds..
Interest Rate Risk Management Elias S. W. Shiu Department of Statistics & Actuarial Science PowerPoint Presentation
Download Presentation
Interest Rate Risk Management Elias S. W. Shiu Department of Statistics & Actuarial Science

play fullscreen
1 / 137
Interest Rate Risk Management Elias S. W. Shiu Department of Statistics & Actuarial Science
169 Views
Download Presentation
billie
Download Presentation

Interest Rate Risk Management Elias S. W. Shiu Department of Statistics & Actuarial Science

- - - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - - -
Presentation Transcript

  1. Interest Rate Risk Management Elias S. W. Shiu Department of Statistics & Actuarial Science The University of Iowa Iowa City, Iowa U.S.A.

  2. Frank M. Redington, F.I.A. “Review of the Principles of Life-Office Valuations” Journal of the Institute of Actuaries Volume 78 (1952), 286-315

  3. Last sentence in the first paragraph: The reader will perhaps be less disappointed if he is warned in advance that he is to be taken on a ramble through the actuarial countryside

  4. Last sentence in the first paragraph: The reader will perhaps be less disappointed if he is warned in advance that he is to be taken on a ramble through the actuarial countryside and that any interest lies in the journey rather than the destination.

  5. For a block of business and for t > 0, let At = asset cash flow to occur at time t (= investment income + capital maturities)

  6. For a block of business and for t > 0, let At = asset cash flow to occur at time t (= investment income + capital maturities)For example, if the company’s assets consist of one 2-year bond with face value of $100 and semi-annual coupons at a nominal annual rate of 6%

  7. For a block of business and for t > 0, let At = asset cash flow to occur at time t (= investment income + capital maturities)For example, if the company’s assets consist of one 2-year bond with face value of $100 and semi-annual coupons at a nominal annual rate of 6% and one 3-year bond at 8%

  8. For a block of business and for t > 0, let At = asset cash flow to occur at time t (= investment income + capital maturities)For example, if the company’s assets consist of one 2-year bond with face value of $100 and semi-annual coupons at a nominal annual rate of 6% and one 3-year bond at 8%, then A0.5 = ½ (6+8) = 7

  9. For a block of business and for t > 0, let At = asset cash flow to occur at time t (= investment income + capital maturities)For example, if the company’s assets consist of one 2-year bond with face value of $100 and semi-annual coupons at a nominal annual rate of 6% and one 3-year bond at 8%, then A0.5 = ½ (6+8) = 7, A1 = 7, A1.5 = 7

  10. For a block of business and for t > 0, let At = asset cash flow to occur at time t (= investment income + capital maturities)For example, if the company’s assets consist of one 2-year bond with face value of $100 and semi-annual coupons at a nominal annual rate of 6% and one 3-year bond at 8%, then A0.5 = ½ (6+8) = 7, A1 = 7, A1.5 = 7, A2 = 103+4 = 107

  11. For a block of business and for t > 0, let At = asset cash flow to occur at time t (= investment income + capital maturities)For example, if the company’s assets consist of one 2-year bond with face value of $100 and semi-annual coupons at a nominal annual rate of 6% and one 3-year bond at 8%, then A0.5 = ½ (6+8) = 7, A1 = 7, A1.5 = 7, A2 = 103+4 = 107, A2.5 = 4, A3 = 104

  12. For a block of business and for t > 0, let At = asset cash flow to occur at time t (= investment income + capital maturities)Lt = liability cash flow to occur at time t (= policy claims + policy surrenders + expenses  premium income)

  13. Let A = Asset Value at time 0. Then,

  14. Let A = Asset Value at time 0. Then, But yield curves are not (necessarily) flat.

  15. Let A = Asset Value at time 0. Then, But yield curves are not (necessarily) flat. Generalize: Then

  16. Similarly, let L = Liability Value at time 0. Then,

  17. Similarly, let L = Liability Value at time 0. Then, Surplus (Net Worth or Equity) = Asset Value - Liability Value = A - L

  18. Similarly, let L = Liability Value at time 0. Then, Surplus (Net Worth or Equity) = Asset Value - Liability Value = A - L Instantaneous interest rate shock: How does the surplus change?

  19. Instantaneous interest rate shock means

  20. Instantaneous interest rate shock means Assume that the asset cash flows {At} and liability cash flows {Lt}do not change as interest rates fluctuate.

  21. Instantaneous interest rate shock means Assume that the asset cash flows {At} and liability cash flows {Lt}do not change as interest rates fluctuate. That is, there are no embedded interest-sensitive options.

  22. Instantaneous interest rate shock means Assume that the asset cash flows {At} and liability cash flows {Lt}do not change as interest rates fluctuate. That is, there are no embedded interest-sensitive options. The more general case of interest-sensitive cash flows is a much harder problem.

  23. Changed asset value is

  24. Changed asset value is Changed liability value is

  25. Changed asset value is Changed liability value is Changed surplus is S* = A* - L*

  26. Question: How will the surplus not decrease?

  27. Question: How will the surplus not decrease? A - L  A* - L*?

  28. Question: How will the surplus not decrease? A - L  A* - L*? Define two (discrete) random variables X and Y: Pr(X = t) =

  29. Question: How will the surplus not decrease? A - L  A* - L*? Define two (discrete) random variables X and Y: Pr(X = t) = Pr(Y = t) = (The cash flowsare assumed to be non-negative.)

  30. Define the function f(t) =

  31. Define the function f(t) = Then

  32. Define the function f(t) = Then

  33. Define the function f(t) = Then

  34. Define the function f(t) = Then

  35. Similarly, L* = L E[f(Y)].

  36. Similarly, L* = L E[f(Y)]. Original Surplus is S = A - L.

  37. Similarly, L* = L E[f(Y)]. Original Surplus is S = A - L. Changed Surplus is S* = A* - L* = AE[f(X)] - LE[f(Y)].

  38. Similarly, L* = L E[f(Y)]. Original Surplus is S = A - L. Changed Surplus is S* = A* - L* = AE[f(X)] - LE[f(Y)]. Now, assume A = L, i.e., assume S = 0.

  39. Similarly, L* = L E[f(Y)]. Original Surplus is S = A - L. Changed Surplus is S* = A* - L* = AE[f(X)] - LE[f(Y)]. Now, assume A = L, i.e., assume S = 0. Then S* = A{E[f(X)] -E[f(Y)]}

  40. Similarly, L* = L E[f(Y)]. Original Surplus is S = A - L. Changed Surplus is S* = A* - L* = AE[f(X)] - LE[f(Y)]. Now, assume A = L, i.e., assume S = 0. Then S* = A{E[f(X)] -E[f(Y)]}, and S*  0 if and only if

  41. Similarly, L* = L E[f(Y)]. Original Surplus is S = A - L. Changed Surplus is S* = A* - L* = AE[f(X)] - LE[f(Y)]. Now, assume A = L, i.e., assume S = 0. Then S* = A{E[f(X)] -E[f(Y)]}, and S*  0 if and only ifE[f(X)] E[f(Y)].

  42. f(t) =

  43. f(t) = In the Redington (1952) model, it = i and = i + , where is a positive or negative constant.

  44. f(t) = In the Redington (1952) model, it = i and = i + , where is a positive or negative constant. Thus f(t) is an exponential function, which is a convex function.

  45. f(t) = In the Redington (1952) model, it = i and = i + , where is a positive or negative constant. Thus f(t) is an exponential function, which is a convex function. In the Fisher & Weil (J. of Business 1971) model, where c is a positive constant.

  46. f(t) = In the Redington (1952) model, it = i and = i + , where is a positive or negative constant. Thus f(t) is an exponential function, which is a convex function. In the Fisher & Weil (J. of Business 1971) model, where c is a positive constant. That is, f(t) = ct

  47. f(t) = In the Redington (1952) model, it = i and = i + , where is a positive or negative constant. Thus f(t) is an exponential function, which is a convex function. In the Fisher & Weil (J. of Business 1971) model, where c is a positive constant. That is, f(t) = ct, which is also a convex function.

  48. Jensen’s Inequality

  49. Jensen’s Inequality: E[f(X)]  f(E[X]) for all convex functions f.